Clinical and genetic evaluation after sudden cardiac arrest - Harris, Stephanie L.; Lubitz, Steven A. (Journal of cardiovascular electrophysiology, 2020)
Sudden cardiac arrest (SCA) and sudden cardiac death (SCD) can be attributed to cardiac, respiratory, metabolic, and toxicologic etiologies. Most cases of SCD are caused by coronary artery disease and approximately 40% of cardiac arrests are unexplained. Inherited arrythmias and cardiomyopathies are important contributors to SCA and SCD. Identifying an inherited condition after such an event not only has important ramifications for the individual, but also for relatives who may be at risk for the familial condition. This review will provide an overview of inherited cardiovascular disorders than can predispose to SCA/SCD, review the diagnostic evaluation for an individual and/or family after an SCA/SCD, and discuss the role of genetic testing.